An Update on Practice Management Instruction in U.S. Dental Schools - Brian M Lange; David G Dunning; Wenyu Qu (Wolters Kluwer Medknow Publications, 2012)
Over the last twenty-seven years, the evaluation of practice man-agement in dental schools has been documented by three studies. In twenty-seven years the teaching of practice management has been influenced by changes in the definition of practice manage-ment, resources available to dental schools, technology, changes in accreditation standards and, more recently, the influence of corpora-tions marketing to dental students. In an effort to determine what resources dental schools are utilizing to teach practice management, fifty-seven schools were contacted, and fifty faculty members with teaching responsibilities were identi-fied. An on-line email survey was administered and results reported at the 2011 meeting of the American Dental Education Association Section on Practice Management. At the section meeting breakout groups discussed two questions. First, identify innovative tools, methods and ideas in the area of practice management. Second, what changes may be necessary to meet recently updated accredi-tation standards 2-17 through 2-19. The recommendations of the breakout groups are presented in detail.